Literature Review: Pengaruh Sorgum Manis sebagai Immunomodulator - Ghina Rania Rizmananda (Lembaga Pengembangan Kinerja Dosen, 2025)
Sweet Sorghum )Sorghum Bicolor) is a group of cereals that have health benefits for the body. There are antioxidant and anti-inflammatory contents in sweet gandrung which are believed to provide immune effects. The study aims to determine the relationship between giving sweet gandrung and the antioxidant and anti-inflammatory activities of sorghum as an immunomodulator through existing clinical and experimental trials. Meta-analysis was conducted by collecting, collecting and analyzing data through 4 relevant journals. Studies were selected based on inclusion and exclusion criteria. The results of the meta-analysis showed that there was a significant difference in giving a sweet gandrung diet with antioxidant activity, decreased lymphocytes (p <0.05) in inflammation. There was a significant effect of giving a dose of sweet gandrung in the form of extract or Jobelyn in reducing lymphocyte levels and showing antioxidant and anti-inflammatory activity that acts as a protector against tissue damage